Factors associated with pulmonary function decline of patients in the cystic fibrosis registry of Turkey: A retrospective cohort study - Emiralioglu, Nagehan; Cakir, Banu; Sertcelik, Ahmet; Yalcin, Ebru; Kiper, Nural; Sen, Velat; Dogru, Deniz (Wiley, 2024)
Background: The decline in pulmonary function is a predictor of disease progression in patients with cystic fibrosis (CF). This study aimed to determine the decline rate of percent predicted forced expiratory volume in 1 s (ppFEV1) based on the data of the CF Registry of Turkey. The secondary aim was to investigate the risk factors related to the decline in ppFEV1. Methods: A retrospective cohort study of CF patients over 6 years old, with pulmonary function data over at least 2 years of follow-up was extracted from the national CF registry for years 2017-2019. Patients were classified according to disease severity and age groups. Multivariate analysis was used to predict the decline in ppFEV1 and to investigate the associated risk factors. Results: A total of 1722 pulmonary function test results were available from 574 patients over the study period. Mean diagnostic age was older and weight for age, height for age, and body mass index z scores were significantly lower in the group of ppFEV1 < 40, while chronic Pseudomonas aeruginosa (p < .001) and mucoid P. aeruginosa colonization (p < .001) were significantly higher in this group (p < .001). Overall mean annual ppFEV1 decline was -0.97% (95% confidence interval [CI] = -0.02 to -1.92%). The mean change of ppFEV1 was significantly higher in the group with ppFEV1 >= 70 compared with the other (ppFEV1 < 40 and ppFEV1: 40-69) two groups (p = .004). Chronic P. aeruginosa colonization (odds ratio [OR] = 1.79 95% CI = 1.26-2.54; p = .01) and initial ppFEV1 >= 70 (OR = 2.98 95% CI = 1.06-8.36), p = .038) were associated with significant ppFEV1 decline in the whole cohort. Conclusions: This data analysis recommends close follow-up of patients with normal initial ppFEV1 levels at baseline; advocates for early interventions for P. aeruginosa; and underlines the importance of nutritional interventions to slow down lung disease progression.
Keywords: cystic fibrosis; FEV1; pulmonary function test; Pseudomonas aeruginosa